Индивидуальный подход к студентам на занятиях музыки - Балгина, А.Д. (My University, 2013)
Urgency of the problem, its social and pedagogical significance determined the choice of the theme of the study "The individual approach to music students in the classroom." The purpose of the study is to develop a model of individualized learning in group activities.